The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00244-016-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Fish Aversion and Attraction to Selected Agrichemicals

Abstract: In agriculture intensive areas, fishponds and natural water bodies located in close proximity to these fields receive water with variable amounts of agrichemicals. Consequently, toxic compounds reach nontarget organisms. For instance, aquatic organisms can be exposed to tebuconazole-based fungicides (TBF), glyphosate-based herbicides (GBH), and atrazine-based herbicides (ABH) that are potentially dangerous, which motivates the following question: Are these agrichemicals attractant or aversive to fish? To answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, both Little et al ( 1990) 43 , and Little and DeLonay (1996) 42 , showed that exposure to a number of different chemicals resulted in reduced activity in rainbow trout (Oncorhynchus mykiss), while Fernandez-Vega et al ( 2002) 44 saw that European eels (Anguilla anguilla) exposed to thiobencarb, an herbicide, reduced motility and increased respiratory frequency. Similarly, Da Rosa et al ( 2016) 45 showed zebra sh (Danio rerio) decreased rotation number when exposed to gamma-Hydroxybutyric acid, or GHB.…”
Section: Discussionmentioning
confidence: 90%
“…For example, both Little et al ( 1990) 43 , and Little and DeLonay (1996) 42 , showed that exposure to a number of different chemicals resulted in reduced activity in rainbow trout (Oncorhynchus mykiss), while Fernandez-Vega et al ( 2002) 44 saw that European eels (Anguilla anguilla) exposed to thiobencarb, an herbicide, reduced motility and increased respiratory frequency. Similarly, Da Rosa et al ( 2016) 45 showed zebra sh (Danio rerio) decreased rotation number when exposed to gamma-Hydroxybutyric acid, or GHB.…”
Section: Discussionmentioning
confidence: 90%
“…Adults exposed to Roundup Original™ (0.00659 µg a.i. mL −1 ) for just 15 s showed behavioral changes, with a decrease in speed and in the number of body rotations [93]. Another study in adults exposed for 96 h to Roundup ® showed a decrease in the distance covered and in mean speed (0.065 and 0.5 µg a.i.…”
Section: Neurotoxicity and Behavioral Changes Caused By Exposure To G...mentioning
confidence: 93%
“…To assess whether zebrafish larvae show either an attractive or an aversive response to chemical exposure, an attraction–avoidance assay can be performed. There are several common experimental designs, such as the Y‐maze (Volz et al 2020), flow‐through chambers (da Rosa et al 2016), and partitioned chambers (Krishnan et al 2014), which allow the fish to make a 2‐choice decision. For this assay, zebrafish of at least 6 dpf are used because all relevant chemosensory systems must be sufficiently developed (De Esch et al 2012).…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…However, zebrafish also showed an attractive response when exposed to harmful stimuli such as herbicide mixtures and psychoactive drugs (Tierney et al 2011; Abreu et al 2016). In some studies, zebrafish have shown an indifferent response (neither attraction nor aversion) to a chemical stimulus, for example, to the tebuconazole‐based fungicide Tebufort DVA and the atrazine‐based herbicide Siptram 500SC, which also may be problematic because the fish do not actively avoid exposure (da Rosa et al 2016).…”
Section: Behavioral Assaysmentioning
confidence: 99%